Pembelajaran IPS Menggunakan Aplikasi Google Classroom Mengenai Kemampuan Berpikir Kreatif Siswa Kelas V - Hardiyanti, Harda; Saputra, Yudha Munajat; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2021)
The advance of technology information in the 4.0 era was grow rapidly and affected to the education system especially in the development of learning methods. This research aims to know about learning plan, learning process and students feedback in order to create the creative thinking skills of 5th grade student in social science through Google Classroom. This research uses a descriptive qualitative method. The research subjects in this study are 5th grade students of SDN Sukatani, Tanjungmedar, Sumedang. The research sample amounted to 20 students consisting of 7 boys and 13 girls. The research results show that the teacherâ€™s plan to do e-learning through Google Classroom was well detailed. Therefore, the influence, feedback, and learning process of 5th grade students of SDN Sukatani while doing e-learning through Google ClassroomÂ  using the google classroom in order to improve creative thinking skills are categorized as moderate.